Titanium dioxide material loaded with graphene and copper nanoparticles and preparation method of titanium dioxide material
By loading graphene and copper nanoparticles on the titanium dioxide microspheres assembled by nanosheets, titanium dioxide/graphene/copper nanoparticles ternary composite materials were prepared, which solved the problem of limited performance of TiO2 photocatalysts and achieved efficient photocatalysis Decompose hydrogen properties of aquatic products.
Patent Information
- Application Number
- CN202411448881.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-07
AI Technical Summary
The band-blocking width of the existing TiO2 photocatalyst is too large, which can only absorb ultraviolet light, and the photogenerated electrons and holes are easy to recombinate, which limits its photocatalytic performance. The existing preparation methods are complex and time-consuming, making it difficult to adapt to industrial needs.
Titanium dioxide microspheres assembled with nanosheets are used as matrix, supported by graphene and copper nanoparticles, and uniformly dispersed titanium dioxide microspheres in an alcohol solvent, and added graphene oxide and copper chloride solution, and then reduced using sodium borohydride to prepare Titanium dioxide/graphene/copper nanoparticle ternary composite material.
The visible light absorption performance of titanium dioxide is improved, the recombination of photogenerated electrons and holes is suppressed, the effective separation of photogenerated carriers is achieved, and the performance of photocatalytic decomposition of aquatic hydrogen is significantly improved.
Smart Images

Figure HDA0005088474420000011 
Figure HDA0005088474420000012 
Figure HDA0005088474420000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic hydrogen production materials, and in particular to a titanium dioxide material carrying graphene and copper nanoparticles and a preparation method thereof. Background Art
[0002] TiO2 has become the most widely studied photocatalyst due to its low price, non-toxicity, good stability, and high light absorption performance. However, the band gap of TiO2 itself is too large, so it can only absorb ultraviolet light, and the photogenerated electrons and holes generated during the catalytic process are very easy to recombine, which seriously limits the photocatalytic performance of TiO2. At present, precious metal loading, introduction of defects, and nanocomposite of carbon materials are considered to be the main means to improve light absorption performance.
[0003] The preparation methods currently studied for the composite catalyst materials of titanium dioxide and graphene and the composite catalyst materials of titanium dioxide and copper include hydrothermal method, sol-gel method, deposition precipitation method, etc., but these methods have disadvantages such as long preparation time and the need for special equipment, and cannot meet the needs of existing industries. There are fewer studies on the preparation of titanium dioxide composite catalyst materials of graphene and copper nanoparticles. Therefore, a titanium dioxide photocatalytic material with simple process, short preparation time and high catalytic activity for photocatalytic water splitting to produce hydrogen is needed. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a titanium dioxide material loaded with graphene and copper nanoparticles in response to the deficiencies of the above-mentioned prior art. While retaining the nanosheet assembly structure of titanium dioxide, it is loaded with graphene and elemental copper nanoparticles and exhibits excellent photocatalytic performance in decomposing water to produce hydrogen as a photocatalyst.
[0005] The technical solution adopted by the present invention to solve the above technical problems is:
[0006] A titanium dioxide material carrying graphene and copper nanoparticles uses titanium dioxide microspheres assembled from titanium dioxide nanosheets as a matrix, and carries graphene and copper nanoparticles on the titanium dioxide microspheres.
[0007] According to the above scheme, the diameter of the titanium dioxide microspheres is generally not more than 5 μm; the nanosheets are slightly curved and the thickness is generally not more than 30 nm.
[0008] The preparation method of the titanium dioxide material carrying graphene and copper nanoparticles comprises the following steps:
[0009] (1) uniformly dispersing titanium dioxide microspheres in a solvent alcohol, then adding graphene oxide, stirring evenly, then adding a copper chloride solution, and stirring evenly again to obtain a precursor solution;
[0010] (2) Sodium borohydride is added to the precursor solution for reduction, thereby obtaining a titanium dioxide material carrying graphene and copper nanoparticles.
[0011] According to the above scheme, the titanium dioxide microspheres are assembled from nanosheets and synthesized using diethylenetriamine as a template. The specific synthesis method is as follows: diethylenetriamine is uniformly dissolved in isopropanol, and then isopropyl titanate is added. After stirring, the resulting mixed solution is transferred to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at a constant temperature of 180-220°C for 16-30h, and then cooled to room temperature, the solid product is separated, washed with anhydrous ethanol, dried, ground into powder, and then transferred to a muffle furnace and calcined at 350-450°C for 1-3h to obtain nanosheet-assembled mesoporous titanium dioxide microspheres TiO2. Wherein, in the mixed solution, the volume ratio of diethylenetriamine, isopropyl alcohol and isopropyl titanate is (0.01-0.03):(10-30):1.
[0012] According to the above scheme, in step (1), the dispersion concentration of titanium dioxide microspheres in the solvent alcohol is 3-5g / L, and the solvent is preferably ethanol; the addition concentration of graphene oxide in the solvent alcohol is 50-100mg / L; and the addition concentration of copper chloride in the solvent alcohol is 0.5-0.8mmol / L. Based on the feed, it can be roughly calculated that in the titanium dioxide material carrying graphene and copper nanoparticles of the present invention, the loading amount of graphene and copper nanoparticles on the titanium dioxide microspheres is approximately between 1% and 3% and between 0.6% and 2%, respectively, calculated as the mass percentage of the two in the titanium dioxide microspheres.
[0013] According to the above scheme, in step (1), cupric chloride is prepared in advance into a cupric chloride solution, preferably with a concentration of 0.04-0.06 mol / L.
[0014] According to the above scheme, in step (2), the concentration of sodium borohydride added to the precursor solution is 50-150 mg / L.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] The present invention uses titanium dioxide microspheres assembled by nanosheets as a matrix, and graphene and metal copper nanoparticles are loaded on the surface of the titanium dioxide microspheres, thus providing a titanium dioxide / graphene / copper nanoparticle ternary composite material; wherein the loading of graphene improves the visible light absorption performance of titanium dioxide, and inhibits the recombination of photogenerated electrons and holes to a certain extent, while the loading of copper nanoparticles further realizes the effective separation of photogenerated carriers, making the titanium dioxide / graphene / copper nanoparticle ternary composite material a very excellent photocatalyst, especially showing excellent photocatalytic water decomposition hydrogen production performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is the SEM image of titanium dioxide microspheres assembled by nanosheets;
[0018] Figure 2 , Figure 3 is a SEM image of the titanium dioxide material loaded with graphene and copper nanoparticles prepared in Example 1;
[0019] Figure 4 is the XRD diagram of the titanium dioxide material and titanium dioxide microspheres loaded with graphene and copper nanoparticles prepared in Example 1;
[0020] Figure 5 This is a graph showing the rate of hydrogen production from photolysis of water by titanium dioxide materials and titanium dioxide microspheres loaded with graphene and copper nanoparticles prepared in Example 1. DETAILED DESCRIPTION
[0021] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with embodiments, but the present invention is not limited to the following embodiments.
[0022] In the following examples, the preparation method of titanium dioxide microspheres used is as follows:
[0023] (1) Add 60 μL of diethylenetriamine to 60 mL of isopropanol and stir for 10 min;
[0024] (2) Add 3 mL of isopropyl titanate to the mixed solution obtained in step (1) and stir for 20 min;
[0025] (3) transferring the mixed solution obtained in step (2) into a polytetrafluoroethylene-lined autoclave, reacting at 200° C. for 24 h, cooling to room temperature, filtering the product, washing with anhydrous ethanol, and drying;
[0026] (4) Grinding the product in step (3) and calcining it at 400° C. in a muffle furnace for 2 h to obtain nanosheet-assembled mesoporous titanium dioxide microspheres TiO2.
[0027] Example 1
[0028] A titanium dioxide material carrying graphene and copper nanoparticles, the specific steps of the preparation method thereof are as follows:
[0029] (1) Add 100 mL of ethanol to a beaker, add 0.4 g of titanium dioxide microspheres while stirring at a constant speed, stir at a constant speed for 10 min, continue to add 4 mL of 2 mg / mL graphene oxide solution, stir at a constant speed for 30 min; then add 1.25 mL of 0.05 mol / L copper chloride solution, stir at a constant speed for 30 min, and obtain a precursor solution;
[0030] (2) Slowly adding 10 mg of sodium borohydride to the precursor solution obtained in step (1) for reduction, stirring continuously for 2 h, and then separating the solid product, washing it three times with anhydrous ethanol and drying it at 60° C. to obtain a titanium dioxide / graphene / copper nanoparticle ternary complex (abbreviated as TiO2-G-Cu-NaHB), which is a titanium dioxide material loaded with graphene and copper nanoparticles. The loading amounts of graphene and copper nanoparticles on the titanium dioxide microspheres are about 2% and about 1%, respectively.
[0031] Depend on Figure 1 It can be seen that the diameter of titanium dioxide microspheres is about 2-3μm, and they are assembled from countless nanosheets. The nanosheets are slightly curved and have a thickness of about 10-20nm.
[0032] Depend on Figure 2 , Figure 3 It can be seen that the titanium dioxide material loaded with graphene and copper nanoparticles prepared in this embodiment maintains the morphology of the titanium dioxide microsphere matrix as a whole and has uniform size, which shows that the reduction of graphene oxide and copper ions using sodium borohydride does not destroy the nanosheet assembly structure of the titanium dioxide matrix; among them, some areas on the surface of the microspheres are covered with flocculent films, which is a morphological feature of graphene, indicating that the reduction method can load graphene on the titanium dioxide surface; and the nanosheets assembled from the titanium dioxide microspheres are composed of crystalline particles, and after loading the elemental copper nanoparticles, there are several nanometer-sized small particles on the surface, which to a certain extent indicates that metal copper particles are loaded on them.
[0033] Comparative Example 1
[0034] The raw material titanium dioxide microspheres of Example 1 were used as comparative example 1 to compare the performance with the titanium dioxide material loaded with graphene and copper nanoparticles prepared in Example 1.
[0035] like Figure 4 As shown, compared with the pure phase titanium dioxide of comparative example 1, the position of the diffraction peak in the XRD pattern of the titanium dioxide material loaded with graphene and copper nanoparticles prepared in Example 1 did not shift, and the half-peak width of the strongest peak did not change significantly, proving that loading graphene and loading metal nanoparticles will not affect the crystal form and crystallinity of titanium dioxide. Figure 4 It can be seen that after the metallic copper nanoparticles were loaded on the titanium dioxide microspheres in Example 1, no characteristic diffraction peak of copper element appeared. This may be due to the fact that the loading content was too low and could not reach the detection accuracy of the X-ray diffractometer.
[0036] Application Examples
[0037] In order to study the photocatalytic performance of the titanium dioxide material loaded with graphene and copper nanoparticles prepared by the present invention, photocatalytic water decomposition and hydrogen production experiments were carried out on Example 1 and Comparative Example 1. The specific steps are as follows:
[0038] 39 mg of the titanium dioxide material loaded with graphene and copper nanoparticles prepared in Example 1 (or the titanium dioxide microspheres used in Comparative Example 1) was added to a mixed solution of 80 mL of anhydrous ethanol and 20 mL of deionized water as a photocatalyst. After ultrasonic dispersion for 15 min, it was transferred to the reaction vessel of the Labsolar-IIIAG photocatalytic device and evacuated, and then placed under a 300W xenon lamp (PLS-SXE300C) for photocatalytic reaction. The wavelength range of the light source is 250-780 nm, the distance between the light source and the liquid surface is adjusted to 15 cm, and the gas sample in the device is collected every hour. A gas chromatograph TCD detector is used to detect the change in H2 gas concentration, and the cumulative collection is 5 hours.
[0039] like Figure 5 As shown, the titanium dioxide material loaded with graphene and copper nanoparticles prepared in Example 1 has a greatly improved performance of photocatalytic hydrogen production compared to the titanium dioxide microspheres in Comparative Example 1. Specifically, the hydrogen production performance of the titanium dioxide material loaded with graphene and copper nanoparticles prepared in Example 1 reaches 14.3 mmol / g / h, which is 60 times that of Comparative Example 1 (0.2 mmol / g / h), indicating that the titanium dioxide / graphene / copper nanoparticle ternary composite material system constructed by the present invention has a significant promoting effect on the photocatalytic performance of titanium dioxide.
[0040] Example 2
[0041] A method for preparing a titanium dioxide material carrying graphene and copper nanoparticles, the specific steps are as follows:
[0042] (1) 100 mL of ethanol was added to a beaker, and 0.3 g of titanium dioxide microspheres was added while stirring at a constant speed, and the mixture was stirred at a constant speed for 10 min. Then, 3 mL of a 2 mg / mL graphene oxide solution was added, and the mixture was stirred at a constant speed for 30 min. Then, 1 mL of a 0.05 mol / L copper chloride solution was added, and the mixture was stirred at a constant speed for 30 min to obtain a precursor solution.
[0043] (2) Slowly adding 10 mg of sodium borohydride to the precursor solution obtained in step (1) for reduction, stirring continuously for 2 h, and then separating the solid product, washing it three times with anhydrous ethanol and drying it at 60° C. to obtain a titanium dioxide / graphene / copper nanoparticle ternary complex (abbreviated as TiO2-G-Cu-NaHB), which is a titanium dioxide material loaded with graphene and copper nanoparticles. The loading amounts of graphene and copper nanoparticles on the titanium dioxide microspheres are approximately 2% and 0.8%, respectively.
[0044] Example 3
[0045] (1) 100 mL of ethanol was added to a beaker, and 0.5 g of titanium dioxide microspheres was added while stirring at a constant speed, and the mixture was stirred at a constant speed for 10 min. Then, 5 mL of a 2 mg / mL graphene oxide solution was added, and the mixture was stirred at a constant speed for 30 min. Then, 1.6 mL of a 0.05 mol / L copper chloride solution was added, and the mixture was stirred at a constant speed for 30 min to obtain a precursor solution.
[0046] (2) Slowly adding 10 mg of sodium borohydride to the precursor solution obtained in step (1) for reduction, stirring continuously for 2 h, and then separating the solid product, washing it three times with anhydrous ethanol and drying it at 60° C. to obtain a titanium dioxide / graphene / copper nanoparticle ternary complex (abbreviated as TiO2-G-Cu-NaHB), which is a titanium dioxide material loaded with graphene and copper nanoparticles. The loading amounts of graphene and copper nanoparticles on the titanium dioxide microspheres are about 2% and about 1%, respectively.
[0047] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A titanium dioxide material carrying graphene and copper nanoparticles, characterized in that: Titanium dioxide microspheres assembled from titanium dioxide nanosheets are used as a matrix, and graphene and copper nanoparticles are loaded on the titanium dioxide microspheres; the titanium dioxide microspheres are micron-sized and do not exceed 5 μm, and the thickness of the nanosheets does not exceed 30 nm; the loading amounts of graphene and copper nanoparticles on the titanium dioxide microspheres are in the range of 1%-3% and 0.6%-2%, respectively.
2. A method for preparing a titanium dioxide material carrying graphene and copper nanoparticles, characterized in that: The following steps are involved: (1) uniformly dispersing titanium dioxide microspheres in a solvent alcohol, then adding graphene oxide, stirring evenly, then adding a copper chloride solution, and stirring evenly again to obtain a precursor solution; (2) Sodium borohydride is added to the precursor solution for reduction, thereby obtaining a titanium dioxide material carrying graphene and copper nanoparticles.
3. The method for preparing a titanium dioxide material carrying graphene and copper nanoparticles according to claim 2, characterized in that: The titanium dioxide microspheres are titanium dioxide microspheres assembled from nanosheets and synthesized using diethylenetriamine as a template. The specific synthesis method is as follows: diethylenetriamine is uniformly dissolved in isopropanol, and then isopropyl titanate is added. After stirring evenly, the obtained mixed solution is transferred to a polytetrafluoroethylene-lined reactor, and the mixture is reacted at a constant temperature of 180-220° C. for 16-30 hours. After cooling to room temperature, the solid product is separated, washed with anhydrous ethanol, dried, ground into powder, and then transferred to a muffle furnace and calcined at 350-450° C. for 1-3 hours to obtain nanosheet-assembled mesoporous titanium dioxide microspheres TiO2.
4. The method for preparing a titanium dioxide material carrying graphene and copper nanoparticles according to claim 3, characterized in that: In the mixed solution, the volume ratio of diethylenetriamine, isopropyl alcohol and isopropyl titanate is (0.01-0.03):(10-30):
1.
5. The method for preparing a titanium dioxide material carrying graphene and copper nanoparticles according to claim 2, characterized in that: In step (1), the dispersion concentration of titanium dioxide microspheres in the solvent alcohol is 3-5 g / L; the addition concentration of graphene oxide in the solvent alcohol is 50-100 mg / L.
6. The method for preparing a titanium dioxide material carrying graphene and copper nanoparticles according to claim 2, characterized in that: In step (1), cupric chloride is prepared in advance into a cupric chloride solution with a concentration of 0.04-0.06 mol / L; the concentration of cupric chloride added in the solvent alcohol is 0.5-0.8 mmol / L.
7. The method for preparing a titanium dioxide material carrying graphene and copper nanoparticles according to claim 2, characterized in that: In step (2), the concentration of sodium borohydride added to the precursor solution is 50-150 mg / L.
8. Use of the titanium dioxide material carrying graphene and copper nanoparticles as claimed in claim 1 as a catalyst in photocatalytic hydrogen production.